Quality Online Teaching and Learning - Chaiyarak , Sakchai; Meepung , Tippawan; Pratsri, Sajeewen (International Journal of Educational Communications and Technology, 2022)
Online teaching has become a new normal in the education industry, a common thing for teachers. Everyone must arrange learning for the learner. The basic characteristics are to manage learning in the same on-time manner as Synchronous Learning. And managing learning in a different way is Asynchronous Learning, which has different ways of managing learning. But to manage quality online learning, there must be a combination of ways to manage learning. By managing face-to-face learning and the online learning characteristics are the reform blended learning. Synchronous and Asynchronous mixes called Hybrid learning create constant interactions with learners, as well as manage learning in a short way. Without providing too much content called microlearning learning, it will make learning a quality learning class.